Towards a Genetic-Based Classification of Human Lung Cancer - Iver Petersen; Simone Petersen (Analytical Cellular Pathology)
Lung cancer is a highly aggressive neoplasm which is reflected by a multitude of genetic aberrations being detectable on the chromosomal and molecular level. In order to understand this seemingly genetic chaos, we performed Comparative Genomic Hybridisation (CGH) in a large collective of human lung carcinomas investigating different tumor entities as well as multiple individual tumour specimens of single patients. Despite the considerable genetic instability being reflected by the well known morphological heterogeneity of lung cancer the comparison of different tumour groups using custom made computer software revealed recurrent aberration patterns and highlighted chromosomal imbalances that were significantly associated with morphological histotypes and biological phenotypes. Specifically we identified imbalances in NSCLC being associated with metastasis formation which are typically present in SCLC thus explaining why the latter is such an aggressive neoplasm characterized by widespread tumor dissemination. Based on the genetic data a new model for the development of SCLC is presented. It suggests that SCLC evolving from the same stem cell as NSCLC should be differentiated into primary and secondary tumors. Primary SCLC corresponding to the classical type evolved directly from an epithelial precursor cell. In contrast, secondary SCLC correlating with the combined SCLC develops via an NSCLC intermediate. In addition, we established libraries of differentially expressed genes from different human lung cancer types to identify new candidate genes for several of the chromosomal subregions identified by CGH. In this review, we summarise the status of our results aiming at a refined classification of lung cancer based on the pattern of genetic aberrations.